A brief clarification to the questionable economics of foreign aid for inclusive human development - Simplice A. Asongu (African Governance and Development Institute (AGDI), 2014)
The study clarifies the questionable economics of foreign aid for inclusive human development. It investigates the effect of a plethora of foreign aid dynamics on the inequality adjusted human development index. Contemporary and non-contemporary OLS, Fixed-effects and a system GMM technique with forward orthogonal deviations are employed. The empirical evidence is based on a sample of 53 African countries for the period 2005-2012. The following findings are established. First, the impacts of aid dynamics with high degrees of substitution are positive. These include, aid for: social infrastructure, economic infrastructure, the productive sector and the multi-sector. Second, the effect of humanitarian assistance is consistently negative across specifications and models. Third, the effects of programme assistance and action on debts are ambiguous because they become positive with the GMM technique. Justifications for these changes and clarifications with respect to existing literature are provided. Policy implications are discussed in light of Piketty's celebrated literature and the post-2015 development agenda. We also provide some recommendations for a rethinking of theories and models on which development assistance is based.
Keywords: B20; F35; F50; O10; O55; 330; Foreign Aid; Political Economy; Development; Africa